Supporting collaboration in multilingual ontology specification: the conceptME approach - Moreira Silva, Manuel (2021)
Despite the availability of tools, resources and techniques aimed at the construction of ontological artifacts, developing a shared conceptualization of a given reality still raises questions about the principles and methods that support the initial phases of conceptualization. These questions become more complex when the conceptualization occurs in a multilingual setting. To tackle these issues a collaborative platform – conceptME - was developed where terminological and knowledge representation processes support domain experts throughout a conceptualization framework, allowing the inclusion of multilingual data to promote knowledge sharing and enhance conceptualization.